Diagnostic accuracy of routine anomaly scans in identifying congenital malformations during the second trimester. A cross-sectional observational study. - Sidar, Chhani Lal Narsingh; Laxmi, Vidya (Student's Journal of Health Research Africa, 2025)
Background: Congenital malformations remain a leading cause of neonatal morbidity and mortality worldwide. Early detection through routine anomaly scans during the second trimester is critical for timely counseling, management, and improving pregnancy outcomes. However, the diagnostic accuracy of these scans varies depending on the type of anomaly and the expertise of the examiner. Objective: To evaluate the diagnostic accuracy of routine second-trimester anomaly scans in detecting congenital malformations when compared with postnatal findings. Methods: A cross-sectional observational study was conducted among 100 pregnant women undergoing routine anomaly scans between 18 and 22 weeks of gestation. Findings were compared with postnatal examinations and confirmatory investigations. Sensitivity, specificity, predictive values, and overall diagnostic accuracy were calculated. Results: Out of 100 cases, routine anomaly scans detected congenital malformations in 18 fetuses (18%). Postnatal evaluation confirmed 20 malformations, including 16 true positives, 2 false positives, and 4 false negatives. Sensitivity was 80%, specificity 97.6%, positive predictive value 88.9%, negative predictive value 95.2%, and overall diagnostic accuracy 94%. Central nervous system anomalies were most common (6%), followed by cardiac (6%), skeletal (5%), renal (3%), and gastrointestinal anomalies (2%). Missed anomalies were primarily subtle cardiac and skeletal malformations. Conclusion: Routine second-trimester anomaly scans demonstrate high diagnostic accuracy, particularly for central nervous system and renal malformations. However, cardiac and skeletal anomalies remain challenging and require meticulous evaluation. Recommendations: Enhanced operator training, incorporation of advanced imaging techniques, and standardized protocols are recommended to improve detection rates of cardiac and skeletal anomalies during routine anomaly scans.